Dialog - Kayam, Umar, 1932-2002. (Jakarta : Metafor, 2005)
Collection of essays by Umar Kayam published between 1969 and 1999.
Includes index.
Keywords: Arts -- Indonesia; Indonesia -- Social conditions; Indonesia -- Social life and customs -- 20th century